2017
DOI: 10.1002/mame.201700211
|View full text |Cite
|
Sign up to set email alerts
|

Selective Laser Sintering 3D Printing: A Way to Construct 3D Electrically Conductive Segregated Network in Polymer Matrix

Abstract: Selective laser sintering (SLS), which can directly turn 3D models into real objects, is employed to prepare the flexible thermoplastic polyurethane (TPU) conductor using self‐made carbon nanotubes (CNTs) wrapped TPU powders. The SLS printing, as a shear‐free and free‐flowing processing without compacting, provides a unique approach to construct conductive segregated networks of CNTs in the polymer matrix. The electrical conductivity for the SLS processed TPU/CNTs composite has a lower percolation threshold of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 45 publications
1
67
0
Order By: Relevance
“…CNT loading was optimized and it was found that 2% CNT scaffold offers the best combination of mechanical behavior and electrical conductivity for scaffold application. Selective laser sintering (SLS) was used by Li et al [86] to prepare the flexible thermoplastic polyurethane (TPU) conductor using self-made MWCNTs wrapped TPU powder. The authors claimed that having lower percolation threshold, the electrical conductivity for the SLS processed TPU/CNTs composite reached ≈10 −1 S/m −1 at 1 wt.…”
Section: Processing Of Carbon Cnt/polymer Nanocomposites Using 3dpmentioning
confidence: 99%
“…CNT loading was optimized and it was found that 2% CNT scaffold offers the best combination of mechanical behavior and electrical conductivity for scaffold application. Selective laser sintering (SLS) was used by Li et al [86] to prepare the flexible thermoplastic polyurethane (TPU) conductor using self-made MWCNTs wrapped TPU powder. The authors claimed that having lower percolation threshold, the electrical conductivity for the SLS processed TPU/CNTs composite reached ≈10 −1 S/m −1 at 1 wt.…”
Section: Processing Of Carbon Cnt/polymer Nanocomposites Using 3dpmentioning
confidence: 99%
“…Additive manufacturing, also known as 3D printing (3DP), is an innovative manufacturing technology which allows one to turn complex 3D models into real objects without special tooling and with extreme facility, cost, and time savings, alongside high accuracy in the realization of specific complex items [1,2]. Additionally, 3DP includes several technologies, such as stereolithography (SLA) [3], fused deposition modeling (FDM) [4], and selective laser sintering (SLS), and some less common techniques [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, 3DP includes several technologies, such as stereolithography (SLA) [3], fused deposition modeling (FDM) [4], and selective laser sintering (SLS), and some less common techniques [5][6][7]. Among them, SLS ensures the highest geometrical freedom and dimensional precision, which allows the manufacturing of parts with well-defined prototypes and components applied in different fields, including electronics, mechanics, and biomedicine [1,8]. Starting from a computer-aided design (CAD) 3D model, SLS builds up objects by sintering and fusing powder material in a layer-by-layer approach, via a computer-controlled laser [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] In order to achieve above purpose, our group has also utilized simple but effective strategies to realize the preparation of high-performance materials with lower ller loading. [27][28][29][30] By using solution dispersion and physical deposition, the llers were selectively coated on the surface of polyamide 11 (PA11) particles. Then, the coated PA11 particles were used for selective laser sintering (SLS), which was also one of the important 3Dprinting technologies.…”
Section: Introductionmentioning
confidence: 99%